Impact of private generators on CO2 emissions in 2024 - مەحەمەد, م. اسامه‌ اشرف محمد; قادر, م.م. دیدار حمد قادر; محمد, محمد (Sulaimani Journal for Humanities, 2025)
One of the most pressing challenges facing humanity today is climate change and global warming, primarily caused by air pollution and the increasing concentration of carbon dioxide (CO₂) in the atmosphere. Among the various sources contributing to air pollution in the Kurdistan Region—and specifically in our study area—are private electricity generators. These generators, commonly used to supply power to households and businesses, emit significant amounts of carbon dioxide (CO₂) during operation. Therefore, we have devoted this research to highlight the impact of private generators on carbon dioxide emissions in 2024. Our research area is the center of Sharazoor district. The aim of this study is to demonstrate the role of specific generators in the emission of carbon dioxide (CO2) from the atmosphere, which contributes to the phenomenon of heat absorption and then has a significant negative impact on their impact on heat balance and change Urban Climate The research method is a descriptive analytical method in which various data are analyzed in the form of tables and maps. The total working hours of all the generators in the study area during the year (2024) was 98,641 hours, and the total gas consumption for all the generators in the study area was 5,622,537 liters, while the total release of carbon dioxide (CO₂) from all the generators in the study area during the year (2024) amounted to 461,976.75 kilograms. If each generator pollutes the surrounding area air within a distance of 50 meters, then the polluted air area per generator in the study area reaches 0.189 km². But if the pollution distance is 100 meters, then the polluted air area reaches 0.49 km². And if the pollution radius extends to 150 meters, then the polluted air area becomes 0.71 km2
Keywords: private electric generators; carbon dioxide CO2; air pollution; Urban environment